Efektivitas Pendayagunaan Dana Zakat dan Infak serta Sedekah Dalam Pemberdayaan Ekonomi Dai (Studi Pada LAZ Baitul Maal Hidayatullah Gerai Samarinda) - Risman Risman; Eny Rochaida; Rabiatul Adawiyah (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2019)
Risman. 2019. Effectiveness of Utilization of Zakat and Infak Funds and Alms in Dai’s Economic Empowerment (Study at LAZ Baitul Maal Hidayatullah Gerai Samarinda). With the supervisor, Prof. Dr. Hj. Eny Rochaida, M.Si and Ms. Rabiatul Adawiyah, Lc., MA.This study aims to explain the effectiveness of the utilization of zakat funds, infak and Sedekah giving in dai economic empowerment in LAZ Baitul Maal Hidayatullah. There are still dai-dai in need of business capital assistance in terms of conducting micro-businesses around Samarinda, especially in the Islamic boarding school Hidayatullah.The type of research used is descriptive qualitative research, in this study the data used is qualitative data that is sourced from primary and secondary data. Data collection is done by observation, interview, documentation, and literature study techniques.The results of this study indicate that LAZ Baitul Maal Hidayatullah Gerai Samarinda has succeeded in utilizing zakat, infaq and alms funds in economic empowerment with a total of 5 successful empowered. The economic empowerment program runs less effectively, because of the lack of funds in economic programs compared to da'wah, education and social programs.Keywords:  Effectiveness, Utilization of ZIS Funds, Economic Empowerment,                        LAZ Baitul Maal Hidayatullah.